2006
DOI: 10.2337/db05-1513
|View full text |Cite
|
Sign up to set email alerts
|

From Clinicogenetic Studies of Maturity-Onset Diabetes of the Young to Unraveling Complex Mechanisms of Glucokinase Regulation

Abstract: Glucokinase functions as a glucose sensor in pancreatic ␤-cells and regulates hepatic glucose metabolism. A total of 83 probands were referred for a diagnostic screening of mutations in the glucokinase (GCK) gene. We found 11 different mutations (V62A, G72R, L146R, A208T, M210K, Y215X, S263P, E339G, R377C, S453L, and IVS5 ؉ 1G>C) in 14 probands. Functional characterization of recombinant glutathionyl S-transferase-G72R glucokinase showed slightly increased activity, whereas S263P and G264S had near-normal acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
75
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 52 publications
10
75
4
Order By: Relevance
“…Our functional study indicates that the R397L mutation has almost no effects on GCK kinetics. Although we found some effect of this mutation on the thermal stability of the enzyme, these effects were relatively mild and not as pronounced as those induced by mutation R308W or previously described mutations such as E265K, E300K or S263P [17,19,31]. It is possible that this mild thermal lability alone might not be sufficient to account for the hyperglycaemia observed in the patients.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Our functional study indicates that the R397L mutation has almost no effects on GCK kinetics. Although we found some effect of this mutation on the thermal stability of the enzyme, these effects were relatively mild and not as pronounced as those induced by mutation R308W or previously described mutations such as E265K, E300K or S263P [17,19,31]. It is possible that this mild thermal lability alone might not be sufficient to account for the hyperglycaemia observed in the patients.…”
Section: Discussioncontrasting
confidence: 62%
“…It is possible that this mild thermal lability alone might not be sufficient to account for the hyperglycaemia observed in the patients. Loss of regulation by GCKR and allosteric activators has been reported for other GCK mutants with increased or nearly-normal enzyme activity [18,31]. Despite this, we found that the R397L mutation did not affect GCK-GCKR binding in vitro and was not located in the allosteric site predicted from the crystal structure [30].…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…In some instances these mutations have been shown to alter enzyme regulation by small molecular activators or glucokinase regulatory protein. In these cases, however, there has been clear support for pathogenicity from co-segregation studies [5,8]. For the remaining variants where co-segregation has not been provided it is possible that these variants, like T342P, are rare polymorphisms.…”
mentioning
confidence: 99%